Digital signal processing system design : LabVIEW-based hybrid programming - Kehtarnavaz, Nasser (Academic Press/Elsevier, 2008)
Reflecting LabViews new MathScripting feature, the new edition of this book combines textual and graphical programming to form a hybrid programming approach, enabling a more effective means of building and analyzing DSP systems. The hybrid programming approach allows the use of previously developed textual programming solutions to be integrated into LabVIEWs highly interactive and visual environment, providing an easier and quicker method for building DSP systems. Features * The only DSP laboratory book that combines both textual and graphical programming * 12 lab experiments that incorporate C/MATLAB code blocks into the LabVIEW graphical programming environment via the new MathScripting feature. * Lab experiments covering basic DSP implementation topics including sampling, digital filtering, fixed-point data representation, frequency domain processing. * Interesting applications using the hybrid programming approach, such as a keypad phone system, a software-defined radio system, and a cochlear implant simulator system * A CD-ROM providing all the lab codes This book is an ideal introduction for engineers and students seeking to develop DSP systems in quick time. * The only DSP project book that combines textual and graphical programming * 12 Lab projects that incorporate MATLAB code blocks into the LabVIEW graphical programming environment via the MathScripting feature. * Interesting applications such as the design of a cochlear implant simulator and a software-defined radio system.